A Metaphorical Conversation: Gadamer and Zhuangzi on Textual Unity. Issue 1 (March 2015) - Mattice, Sarah
Abstract: In Truth and Method, Gadamer asserts that prior to beginning the process of understanding a text, we make certain assumptions about the text being a unity modeled on a one‐on‐one conversation. How should we approach a text that was composed by so many authors over such a long span of time? Using resources from the Zhuangzi, I argue for expanding the metaphor across time, space, and identity in order to rethink Gadamer's assumption and its operative metaphor.